2021
DOI: 10.46827/ejoe.v6i1.3529
|View full text |Cite
|
Sign up to set email alerts
|

Greek University Students’ Attitudes About Distance Education Due to Emergency Circumstances

Abstract: Emergencies like Covid-19 brought distance education to the fore, as countries were forced to close the campuses and initiate online teaching. Many universities in the country supported a distance education program aimed at students who had experienced an unprecedented experience. Thus, 155 students from the Greek department of Early Years Learning & Care participated in the present study, which aimed to investigate the factors that influence learners’ perceptions and attitudes during distance learning. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Another study conducted with the pre-service teachers from the Department of Computer and Instructional Technologies reported that the students exhibited a positive attitude towards distance education and that the positive attitude was directly related to the year of study (Durmus & Kaya, 2011). Other studies with similar findings were also found in the literature (Dikbaş, 2006;Gultekin, 2006;Karavida et al, 2021).…”
Section: Introductionmentioning
confidence: 57%
“…Another study conducted with the pre-service teachers from the Department of Computer and Instructional Technologies reported that the students exhibited a positive attitude towards distance education and that the positive attitude was directly related to the year of study (Durmus & Kaya, 2011). Other studies with similar findings were also found in the literature (Dikbaş, 2006;Gultekin, 2006;Karavida et al, 2021).…”
Section: Introductionmentioning
confidence: 57%
“…This result is consistent with the findings obtained in the studies carried out by Ağır (2007) and Akyürek (2021). The lack of technical support and the inability to connect also played a key role in the negative evaluation of distance education (Karavida, 2021). The age of the teachers at the beginning of their profession, their technology competencies, their digital skills being at a higher level, and the fact that young teachers are more open and adaptable to new methods and techniques in education can explain the more positive attitudes of young teachers in the profession towards distance education.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 99%
“…Ağır (2007) and Akyürek (2021) stated that teachers who have sufficient knowledge about distance education have a more positive attitude than other teachers. Karavida (2021) reported that the flexibility of learning makes the learning process more interesting, as do the different pedagogical tools and resources used in virtual classes. The finding of Hebebci et al (2020) that teachers demand in-service training to improve distance education also supports this result.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research by Vasiliki et al examining the perceptions and attitudes of university students towards distance education during Covid 19 period showed that many participants ended their education due to low speed internet connection and system failures and in addition to the feelings of the students, the support provided by instructors to the students was also important during distance education process and these factors affected the satisfaction of students from distance education. The students also stated that they did not understand all survey questions (Vasiliki et al, 2021).…”
mentioning
confidence: 99%